Social media interactions between government and the public: A Chinese case study of government WeChat official accounts on information related to COVID-19 - Shao, Chang’an; Guan, Xin; Sun, Jiajing; Cole, Michael; Liu, Guiying (Frontiers in Psychology, 2022)
The concept of a public energy field is central to public administration discourse theory. Its main idea is the facilitation of dialogue between government and the public, on the basis of equality, in order to construct a public policy consensus. In contemporary society, social media provides new and distinctive channels for such interactions. Social media can, therefore, be conceived as novel type of public energy field. Since the outbreak of the COVID-19 pandemic, interactions between the Chinese government and the Chinese public have been acutely reflected through WeChat official accounts. This article focuses on the COVID-19 pandemic and, through social media text mining and processing, analyzes the text topics and emotions covered. Basic principles of discourse validity, regarding this public energy field and two guarantee conditions, are applied to analyze the information exchange and dialogue between government and the public on COVID-19 through WeChat official accounts. It is found that the WeChat official accounts supplied a harmonious dialogue space for the government and the public. However, according to the four principles of discourse legitimacy, the government WeChat official accounts have not yet formed a harmonious dialogue space to balance the public energy field, and the interaction between the government and the public has to be improved. Government’s social discourse had a significant influence the public’s social discourse. Using text analysis, the study find that government has published information on 11 topics related to the prevention and control of the epidemic, and it shows the guidance of emotion and information. It can be argued that the public energy field presented by both the government and the public effectively portrayed and reflected the actual situation of the pandemic in China.